Performance Evaluation Strategy and its Impact on the Achievement of Organizational Effectiveness - علك, عبد الناصر; رزوقي, نبراس ناجي (Journal of Economics and Administrative Sciences, 2017)
AbstractThe research aims to determine the impact of the strategy performance evaluation and of the Standards (leadership, people, knowledge, processes, financial) in the achievement of organizational effectiveness in accordance with the dimensions (planning and setting goals, Exploitation of the Environment, achieve the goals, the ability to adapt, information management and communications) and the relationship between them, the problem of the research in the growing interest in the process of performance evaluation for organizations, the erroneous belief that the performance evaluation activity is useful, and the fact that performance evaluation process is one of the main tasks of the work of the Office of the Inspector General, according to the Order (57) for the year (2004), , turn the researcher to select a sample search of the Inspector General's Office staff, amounting to questionnaires approved (73) questionnaire was used statistical package SPSS in data processing and analysis, and in the light of the findings and conclusions of which the most important was the staff interact with the adoption of a strategy to evaluate performance, it has been the formulation of a number of recommendations, the most important was the need for the Office of the Inspector General staff about the importance of the work according to internationally recognized standards within the strategy to evaluate the performance, because of its impact on the interaction with them on the ground to get to the target organizational effectiveness